Management of Reputation Risks at the Agricultural Enterprises of Eastern Europe as a Component of Increasing Their Competitiveness - Zakharchenko, Oleg V.; Eremina, Alina R.; Ushakov, Denis S.; Odintsov, Oleh M.; Mylnichenko, Serhii M. (Journal of Reviews on Global Economics, 2021)
We note a significant role of the agricultural sector in the development of economic systems in a significant number of post-Soviet countries of Eastern Europe. However, Eastern European agricultural enterprises have significant problems in ensuring and managing their competitiveness, where reputation and the risks associated with it are of key importance. Novelty. The scientific novelty of the research paper is the developed algorithm of reputation risk management, which is based on the author’s methodology of their evaluation and takes into account the peculiarities of such management in agricultural enterprises from the post-Soviet countries of Eastern Europe. To achieve the goal and test the hypotheses put forward in the research paper, a set of general, specific and technical methods were used at the empirical and theoretical levels, such as: abstraction method; expert method; methods of analysis and synthesis; comparison; deduction; induction; methods of systematization, grouping and logical generalization. The research methodology is based on systemic and functional, historical and systemic approaches in identifying and resolving the range of problems of reputation risk management within the framework of improving the competitiveness management of agro-industrial enterprises from the post-Soviet countries of Eastern Europe. For the purpose of the study, data were collected and an empirical analysis was conducted concerning the eleven Eastern European countries that were part of the Soviet Union for 1991-2018 regarding analysis of the dynamics of agricultural production and its share in GDP according to statistics taken from the KNOEMA databases. Policy considerations: the agricultural sector of the economy plays an increasing role in the economic systems of some post-Soviet countries of Eastern Europe, serving as the basis for their sustainable development; agricultural producers from the post-Soviet space of Eastern Europe have problems with ensuring competitiveness in national, international and world markets; reputation risk plays a significant role in ensuring and improving the competitiveness management of agricultural enterprises from post-Soviet countries of Eastern Europe; the formation of an effective reputation risk management algorithm is a key element in ensuring and improving the competitiveness management of Eastern European agricultural producers.